(3JMdjd GdHjGfGJ HGSJNOGe HQfGeL (BSPSSs - (3QVG YHO Gddg(B, (3CHh SQjYs ((3YeGf(B:s (3OGQ GdacQ(B,s, 2004)
(3GYOGO NWI dJQejR GdHjGfGJ, GONGd GdHjGfGJ Edi GdHQfGeL, GdGMUGA GdhUaj ddHjGfGJ hJeKjdgG HjGfjG, ebGQfI GdeJhSWGJ, JMdjd GdJHGjf, GdGQJHGW hGdGfMOGQ, GdGNJHGQGJ GdGMUGFjI GdCHGQGeJQjI, KHGJ GdGNJHGQ, GdJMdjd GdYGedj, GdQShe GdHjGfjI, GdeQGLY hGdedGMb(B.s
(3GdeQGLY U(B.221s
Keywords: (3GdEMUGA GdhUaj(B- (3GdMGSHGJ GdcJQhfjIs; (3GdHjGfGJ GdGMUGFjI(B- (3HQfGeL (BSPSSs